Kultum Sebagai Sarana Pengembangan Public Speaking Mahasiswa Di Ma'had Al-Jami'ah UIN Raden Intan Lampung: PENDAHULUAN,TEORI KULTUM,PUBLIC SPEAKING,HASIL PEMBAHASAN,KESIMPULAN - Anwar, Ahmad Saipul; Baharudin; Rudy Irawan; Uswatun Hasanah; Terna Kuswanto (Qolamuna : Jurnal Studi Islam, 2025)
This study aims to explore the role of kultum (Seven Minute Lecture) as a means of developing public speaking skills as well as English and Arabic foreign language skills for students at Ma'had Al-Jami'ah UIN Raden Intan Lampung. Kultum not only serves as a medium for delivering religious messages, but also as a platform to train studentsin expressing their opinions and ideas in front of an audience. Through this activity, students are expected to increase self-confidence, mastery of material, and communication skills that are essential in social interaction. This study uses a qualitative approach with interview and documentation methods to collect data from students who have implemented the cultum. The results showed that the kultum contributed significantly to reducing nervousness and improving public speaking ability, which are important skills in daily life and career development. Thus, cultum becomes an effective tool in building students' soft skills, supporting individual successin interacting with society. Keywords: Kultum, Public Speaking, Ma'had Al-Jami'ah, Skill Development, Self Confidence